Penegakan Hukum terhadap Penyelundupan Pakaian Bekas - Dita Birahayu (Faculty of Law Hang Tuah University, 2020)
Indonesia is a maritime country that has a wider sea area than land area. Sea provides great benefits for the people of Indonesia, including sources of life for fishermen, transportation routes, recreation areas, sources of electricity generation and sources of foreign exchange. Sea transportation is more efficient than land and air, besides providing positive benefits there is also a negative side of sea transportation, one of which is the illegal smuggling of goods. Smuggled goods are not only in the form of daily necessities, including waste generated from daily activities such as used clothing. The state loss caused by smuggling used clothing reaches trillions of rupiah.